2004
DOI: 10.1111/j.1600-0714.2004.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin and fibronectin expression in odontogenic cysts

Abstract: Our results demonstrate differences between the expression of ECM proteins in the OCs studied. The higher tenascin and fibronectin expression in the capsule of OKCs suggests marked instability in the cystic structure and may contribute to its aggressive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
22
3
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 46 publications
10
22
3
4
Order By: Relevance
“…Murata et al [30] and Poomsawat et al [13] suggested that AOT cells, like pre-ameloblasts, are able to synthesize ECM proteins due to the presence of Wbronectin inside the luminal spaces of duct-like structures. Although this latter Wnding could not be veriWed in the present study, the focal positivity for Wbronectin in epithelial cells of AOT conWrms the capacity of these cells to synthesize this glycoprotein [13,29]. Further analysis of our results showed that Wbronectin expression is more intense at the epithelial-mesenchymal interface of both solid ameloblastomas and AOT, showing a linear and discontinuous distribution in most cases, a fact also reported by Heikinheimo et al [28].…”
Section: Discussionsupporting
confidence: 60%
“…Murata et al [30] and Poomsawat et al [13] suggested that AOT cells, like pre-ameloblasts, are able to synthesize ECM proteins due to the presence of Wbronectin inside the luminal spaces of duct-like structures. Although this latter Wnding could not be veriWed in the present study, the focal positivity for Wbronectin in epithelial cells of AOT conWrms the capacity of these cells to synthesize this glycoprotein [13,29]. Further analysis of our results showed that Wbronectin expression is more intense at the epithelial-mesenchymal interface of both solid ameloblastomas and AOT, showing a linear and discontinuous distribution in most cases, a fact also reported by Heikinheimo et al [28].…”
Section: Discussionsupporting
confidence: 60%
“…There are few reports available in the literature regarding tenascin expression and its role in odontogenic tumors (4,9,20). In our study, tenascin positivity was more prominent in the KOT connective tissue wall compared to the RCs and DCs.…”
Section: Discussionsupporting
confidence: 44%
“…ECM proteins have been detected in several odontogenic cysts and tumors, 7,8,[17][18][19] but no investigation has explored the relationship between collagen IV, MMPs, and TIMPs in odontogenic cysts and tumors.…”
Section: Discussionmentioning
confidence: 99%